The use of TED and YOUTUBE in Extensive Listening Course: Exploring possibilities of autonomy learning - Saputra, Yuyus; Fatimah, Asri Siti (Universitas Katolik Indonesia Atma Jaya, 2018)
This study explores how extensive listening can utilize internet based-media, namely TED and YouTube. The study also examines the researcherâs reflection on his teaching practice by adopting the participatory action research framework. Participating in this study are EFL freshmen of a state university in Indonesia during the Extensive Listening course. The findings showcase several changes in the teaching-learning circumstances that affect the implementation of in-class activities. The students share that YouTube and TED help them enrich their English vocabulary. Further, they also state that the tasks create a more dynamic and less monotonous learning atmosphere. Overall, the use of YouTube and TED can be designed to be effective instructional media for Extensive Listening tasks.